Building a Pedagogy of Writing Transfer Through an Undergraduate Journal Publication - Kaitlyn Harris; Paige France; Christopher Eaton (Language and Literacy: A Canadian Educational e-journal)
Despite effective knowledge transfer being a primary goal among post-secondary instructors, scholars, and administrators, students still have difficulty adapting their skills to novel contexts. This challenge is especially salient in writing pedagogy, where the transfer of writing-related knowledge is not guaranteed (Driscoll, 2011; Perkins & Salomon, 2012). To investigate possibilities for catalyzing writing transfer, this paper reports on a collaborative autoethnography project (Chang et al., 2013) carried out by two undergraduate students and a faculty member based at a large Ontario university. Their experiences on the editorial team of a first-year writing journal provide insight into how mentorship within journal environments can contribute to post-secondary students’ literacy development, and, concurrently, help them to transfer what they know to new contexts. We consider how similar learning opportunities may contribute to undergraduate skill development outside traditional classroom contexts.